Superlattice deformation in quantum dot films on flexible substrates via uniaxial strain. Issue 3 (31st January 2023) - Heger, Julian E.; Chen, Wei; Zhong, Huaying; Xiao, Tianxiao; Harder, Constantin; Apfelbeck, Fabian A. C.; Weinzierl, Alexander F.; Boldt, Regine; Schraa, Lucas; Euchler, Eric; Sambale, Anna K.; Schneider, Konrad; et al.
Abstract : Superlattice deformation in PbS quantum dot thin films introduced by uniaxial strain: In situ GISAXS study on the correlation of morphology and photoluminescence. Abstract : The superlattice in a quantum dot (QD) film on a flexible substrate deformed by uniaxial strain shows a phase transition in unit cell symmetry. With increasing uniaxial strain, the QD superlattice unit cell changes from tetragonal to cubic to tetragonal phase as measured with in situ grazing-incidence small-angle X-ray scattering (GISAXS). The respective changes in the optoelectronic coupling are probed with photoluminescence (PL) measurements. The PL emission intensity follows the phase transition due to the resulting changing inter-dot distances. The changes in PL intensity accompany a redshift in the emission spectrum, which agrees with the Förster resonance energy transfer (FRET) theory. The results are essential for a fundamental understanding of the impact of strain on the performance of flexible devices based on QD films, such as wearable electronics and next-generation solar cells on flexible substrates.